Influence of Atraumatic Restorative Treatment and its therapeutic indication against infected and affected tissue: a narrative review (Research, Society and Development, 2022)
Atraumatic Restorative Treatment, known as ART (Atraumatic Restorative Treatment), is a technique that uses only manual excavators and curettes to remove decayed tissue. Subsequently, an adhesive restorative material is applied, such as glass ionomer cement (GIC), which has the advantage of releasing fluoride. This technique uses selective removal of carious tissue, removing only infected dentin and maintaining the affected dentin. Thus, the objective of this review is to carry out about ART, its characteristics, advantages and limitations during the therapeutic decision regarding the infected and affected tissue. A search was carried out through the PubMed and BVS databases, from 2013 to 2022, with the keywords: Dental Caries AND Dentin AND Caries-affected dentin. The ART technique is indicated for both primary and permanent teeth. It is a simple, easy-to-perform, low-cost, painless technique that does not require the use of a high-speed pen and the use of local anesthesia. This technique has some limitations such as the size and retention of the cavity, quality of the restorative material and, mainly, the low acceptance of the technique by the professional and community. Guidance should be monitored with control queries. It is possible to conclude that ART is a technique of wide social reach, reducing clinical time, being easy to apply both in the dental chair and in places without equipment. However, it requires training and qualification of the operator and assistant.